A199 GLYCOGENIC HEPATOPATHY: HEPATIC MANIFESTATION OF POORLY CONTROLLED DIABETES MELLITUS. (15th March 2019) - AlAli, M; Fathi, M; AlAli, A
Abstract: Background: Elevated liver enzymes is a common clinical problem encountered in patients with Diabetes Mellitus (DM). There are multiple etiologies, the most common being Non-Alcoholic Fatty Liver Disease (NAFLD). Glycogenic Hepatopathy (GH) is a rare condition characterized by glycogen deposition in the liver in patients with poorly-controlled type 1 DM. GH usually presents with abdominal pain and elevated transaminases. The diagnosis requires liver biopsy to confirm characteristics pathological findings. The condition is fully reversible with tight control of blood glucose Aims: To describe the typical clinical and pathological features of GH in a patient with DM and the appropriate management of such condition once recognized Methods: Illustrative case report and review of current peer-reviewed literature Results: We present a case of a 20-year-old female with a 12-year history of poorly controlled DM type 1. She was referred to the liver clinic for the evaluation of persistently elevated liver enzymes for more than a year. Her physical examination was normal. Blood test revealed elevated aminotransferases (AST 1235 IU/L, ALT 357 IU/L, ALP 211 IU/L, and GGT 538 IU/L). She had normal liver synthetic function, and a HbA1c 15%. Transabdominal ultrasound revealed normal looking liver with normal size. A liver biopsy was done to determine the exact etiology of her liver disease. The biopsy showed pale swollen hepatocytes with cytoplasmic rarefaction and glycogen deposits that were PAS positive and diatase negative, which was consistent with GH. The patient was referred to an endocrinologist for better control of her DM. Following the control of her blood glucose, her liver enzymes improved markedly and eventually normalized within 2 months. At 1-year follow-up, her blood glucose remains well-controlled and her liver enzymes continue to be normal. A review of the literature reveals that GH is an uncommon condition that affects patients with poorly controlled DM, typically type 1. It presents with non-specific symptoms and associated with elevated liver enzymes in a hepatocellular pattern that can be quite marked. The diagnosis is typically made by liver biopsy which shows characteristic findings including pale swollen hepatocytes with minimal or absent steatosis and fibrosis in addition to glycogen accumulation in the cytoplasm and nuclei of hepatocytes by PAS stain. The mainstay of treatment of GH is tight control of blood glucose which results in complete normalization of the liver enzymes and the histological changes. The prognosis is excellent with no long-term sequelae once the condition is treated Conclusions: GH is a rare, yet important, liver pathology that is seen almost exclusively in patients with poorly controlled DM. Increasing clinicians awareness of this condition helps in establishing earlier diagnosis, instituting appropriate therapy and ultimately improving patients outcome Funding Agencies: None